Purchasing Cycle Analysis: A Case Study of PT Sri Rejeki Isman Tbk - Syahqim Sudarpo; Firmansyah Firmansyah; Thytis Hidayah; Fara Husni Fadhillah (Brilliant International Journal Of Management And Tourism, 2026)
The role of Accounting Information Systems in a company is to provide accurate and appropriate information to support company management in processing decision making to control and supervise the company's operational activities. This study was conducted with the aim of analyzing and understanding the purchasing cycle running at PT. Sri Rejeki Isman Tbk, and assessing whether there are weaknesses in the system. After the analysis is carried out, if weaknesses are found, a solution will be made in the form of a manual system design proposal. This research is a qualitative descriptive study. Based on the research that has been done, the results show that there are problems, problems that exist in the purchasing cycle of PT. Sri Rejeki Isman are the accumulation of debt to suppliers, weak internal controls in the purchasing process. Poor financial management can affect the company resulting in the company being unable to purchase materials ideally, resulting in a negative impact, namely a decrease in operational performance and production disruptions. This study shows that weaknesses in the purchasing cycle contribute to the company's operational instability and worsen conditions leading to bankruptcy. These weaknesses need to be improved by carrying out the effectiveness of the purchasing cycle and internal controls in maintaining the company's sustainability.